2019
DOI: 10.3390/ijerph16193778
|View full text |Cite
|
Sign up to set email alerts
|

Can Asset-Based Community Development with Children and Youth Enhance the Level of Participation in Health Promotion Projects? A Qualitative Meta-Synthesis

Abstract: The asset-based community development (ABCD) approach have been widely used to map local assets and to ensure participation of local communities in public health promotion strategies. Participatory practices, such as ABCD, have been applied to shift public health strategies towards addressing health inequities. In this meta-synthesis, we ask if, and how, ABCD enhance the level of participation for children, youth and schools. Three thousand eight hundred eight titles and abstracts were identified in ten databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…One of those strategies is strengthening community action, which focuses on empowering communities to set priorities, make decisions, and implement plans to improve health and well-being. This strategy is consistent with other health and social science research such as community development and compassionate communities [ 3 – 5 ]. Community-led solutions have long been an important means to address interconnected health and social issues, such as homelessness and food insecurity [ 6 , 7 ].…”
Section: Introductionsupporting
confidence: 61%
“…One of those strategies is strengthening community action, which focuses on empowering communities to set priorities, make decisions, and implement plans to improve health and well-being. This strategy is consistent with other health and social science research such as community development and compassionate communities [ 3 – 5 ]. Community-led solutions have long been an important means to address interconnected health and social issues, such as homelessness and food insecurity [ 6 , 7 ].…”
Section: Introductionsupporting
confidence: 61%
“…One of those strategies is strengthening community action, which focuses on empowering communities to set priorities, make decisions, and implement plans to improve health and well-being. This strategy is consistent with other health and social science research such as community development and compassionate communities [3][4][5]. Community-led solutions have long been an important means to address interconnected health and social issues, such as homelessness and food insecurity [6,7].…”
Section: Introductionsupporting
confidence: 55%
“…In agreement with our review, McLean and McNeice (2012) as cited in Friedli [19] have observed that many asset mapping studies or projects are "case study" assessments, rendering it impossible to answer questions about the effectiveness of such interventions, because an asset-based approach to public health assumes certain inherent community circumstances that render more traditional assessment methods, such as the randomised control trial, less useful and at times inappropriate [20]. Similarly to our review, Agdal, Midtgard and Meidell [103] observed that the participatory action research (PAR) method is used as a foundation for the mapping process.…”
Section: Discussionmentioning
confidence: 78%